2012
DOI: 10.2319/042312-339.1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of dentoskeletal changes in Class II division malocclusion treatment with twin force bite corrector

Abstract: Objective: To evaluate the dentoskeletal changes of Class II malocclusion treatment with the Twin Force Bite Corrector (TFBC). Materials and Methods: The sample comprised 86 lateral cephalograms obtained from 43 subjects with Class II division 1 malocclusion; the subjects were divided into two groups. The experimental group comprised 23 patients with a mean initial age of 12.11 years who were treated with the TFBC for a mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 15 publications
6
18
0
8
Order By: Relevance
“…Also upper incisor inclination to NA and upper incisor position relative to NA were significantly decreased. These results agreed with other studies on PowerScope (6,8) .Similar results were reported with TFBC (14)(15)(16) with AdvanSync (12,13) and with Eureka Spring (20) .…”
Section: Regarding the Skeletal Changessupporting
confidence: 92%
See 2 more Smart Citations
“…Also upper incisor inclination to NA and upper incisor position relative to NA were significantly decreased. These results agreed with other studies on PowerScope (6,8) .Similar results were reported with TFBC (14)(15)(16) with AdvanSync (12,13) and with Eureka Spring (20) .…”
Section: Regarding the Skeletal Changessupporting
confidence: 92%
“…This reduction in overbite might be attributed to proclination of the lower incisors in combination with the anterior edge to edge relationship which left the buccal segment out of occlusion and gave the chance for normal buccal segment vertical growth. Studies on TFBC reported reduction in the overbite with a mean value of -3.2mm (15,16) which is very close to the results of this study. Significant decrease for the overbite with a mean value -2.4mm was reported from a study on Herbst appliance (21,22) and another study on Jasper Jumper appliance (24) Regarding the inter-incisal angle, this study showed significant increase with a mean of 10º.…”
Section: Regarding the Skeletal Changessupporting
confidence: 89%
See 1 more Smart Citation
“…The study design was retrospective and involved a systematic analysis of all Class II patients treated with the TFBC appliance 16,17 Subjects fulfilling the following requirements were selected: (1) Class II molar relation, defined as having at least an ''end on'' molar relation with no subdivision malocclusion, (2) ANB angle $ 3.5u, (3) SN-GoGn # 36u, (4) Overjet $ 3.5 mm, and (5) up to 3-4 mm crowding or spacing. The initial data pool consisted of 51 consecutively treated Class II patients who were divided into two groups of prepubertal and postpubertal samples based on the modified cervical vertebral maturation stage (CVMS) by Bacetti et al 18 This method was chosen because appearance of concavity at the lower border of C4 (which occurs at onset of stage III, ie, past the pubertal growth spurt) is easily identifiable.…”
Section: Methodsmentioning
confidence: 99%
“…To minimize the mandibular incisor proclination during the fixed functional appliance phase, mandibular incisor brackets with 26u torque were used. The Twin Force Bite Corrector (TFBC) appliance [17][18][19] was used for 10 months for Class II correction (Figure 4). The patient was in a super Class I molar relation with anterior edge-to-edge incisal relationship to compensate for mild relapse after removal of the TFBC appliance.…”
Section: Treatment Progressmentioning
confidence: 99%